The Culture of Capital Punishment in Japan - Johnson, David T. (Palgrave Advances in Criminology and Criminal Justice in Asia,, 2020)
This open access book provides a comparative perspective on capital punishment in Japan and the United States. Alongside the US, Japan is one of only a few developed democracies in the world which retains capital punishment and continues to carry out executions on a regular basis. There are some similarities between the two systems of capital punishment but there are also many striking differences. These include differences in capital jurisprudence, execution method, the nature and extent of secrecy surrounding death penalty deliberations and executions, institutional capacities to prevent and discover wrongful convictions, orientations to lay participation and to victim participation, and orientations to "democracy" and governance. Johnson also explores several fundamental issues about the ultimate criminal penalty, such as the proper role of citizen preferences in governing a system of punishment and the relevance of the feelings of victims and survivors.